Phytochemical and anti bacterial studies of leaves of Rosmarinus officinalis cultivated in Karbala, Iraq. - Amani A. Tawfeeq; Monther F. Mahdi; Ibrahim S. Abaas; Ali Hussein Alwan (College of Pharmacy / Mustansiriyah University, 2018)
Rosmarinus officinalis is one of the important bioactive medicinal plants belongs to labiatae family. The aim is to identifying the essential oil and rosmarinic acid extracted from rosemary leaves and to evaluate its anti bacterial activity. Gas Chromatography-Mass analysis was performed for essential oil of rosemary and HPTLC analysis was done for 90% methanolic extract of rosemary leaves. Rosmarinic acid was detected and The essential oil content was 1.5% and characterized with high amount of 1,8 cineol (53.63%) . The zone of inhibition of some bacteria was estimated. Our findings showed that rosemary leaves has Good percentage of rosemary phytochemicals (essential oil and rosmarinic acid) and has significant antibacterial activity against different species of bacteria.